Examining the Factors Affecting the Employment Increase of Enterprises in Turkey - GİRAY YAKUT, SELAY (My University, 2019)
An increase in employment is an important dynamic that contributes to the growth of countries. Labor force, technology, sizeand age of enterprises are defined as effective factors in the literature. Nevertheless, trouble-free processes in financialopportunities, infrastructure and regulatory agencies have supportive effects. Troubles in these processes are known asobstacles to growth of enterprises. In this study, dynamics and obstacles, as well as other factors that affect employmentincrease have been analyzed using World Bank Enterprise Survey (2015) for 6006 enterprises that are operating in Turkey. Withreference to knowledge in this survey, the increases in the number of employees between the years of 2012 and 2014 werecalculated. These increases were transformed into a categorical variable. The relationship between this categorical variable withthe gender of executives, educational level of executives, the industry that enterprise belongs to, the age of the enterprise, thesize of enterprise and obstacles were investigated. Multiple correspondence analysis and logistic regression were used in theanalysis. According to the findings, the age of the enterprises, the educational level of executives, the industry that the enterprisebelongs to, inadequately educated employees, political instability as well as tax administration have an effect on increases inemployment.

İstihdam artışı ülke ekonomisinin büyümesine katkıda bulunan bir dinamiktir. Literatürde, beşeri sermaye, teknoloji, işletmelerin büyüklüğü ve yaşı işletmelerin büyümesinde etkili olan faktörler olarak sıralanır. Bununla beraber altyapıda, finansal olanaklarda ve düzenleyici kuruluşlarda sorunsuz işleyiş işletmelerin büyümesi üzerinde destekleyici bir etkiye sahiptir. Ancak bu yapıda karşılaşılan aksaklıklar, işletmelerin büyüme konusunda karşılaştıkları engellerdir. Bu çalışmada, istihdam artışını etkileyen dinamikler ve yanı sıra engeller, Dünya Bankası’nın düzenlediği 2015 yılı İşletme Anketlerinden faydalanılarak, Türkiye’de faaliyet gösteren 6006 işletme üzerinden değerlendirilmiştir. Bu ankette yer alan 2012 ve 2014 yılı çalışan sayıları bilgisinden hareketle istihdam artışları hesaplanmış ve bu artışlar kategorik veriye dönüştürülmüştür. Elde edilen bu kategorik değişken ile yöneticilerin cinsiyeti, eğitim düzeyi, işletmenin yer aldığı sektör, işletmenin yaşı, büyüklüğü, işletmelerin karşılaştıkları engeller arasındaki ilişki incelenmiştir. Çalışmada çoklu uyum analizi ve lojistik regresyon analizlerinden faydalanılmıştır. Elde edilen bulgulara göre, işletmenin yaşı, yöneticinin eğitim düzeyi, sektör, yetersiz eğitimli işgücü, politik istikrarsızlık ve vergi yönetimi işletmelerin istihdam artışı üzerinde etkili olan değişkenlerdir.
Türkiye’deki İşletmelerin İstihdam Artışını Etkileyen Faktörlerin İncelenmesi
Keywords: İstatistik ve Olasılık; İktisat; İşletme